Hubungan Pengetahuan dengan Sikap Masyarakat pada Penggunaan Antibiotik di Kelurahan Pondok Besi Kota Bengkulu - Miftahuljannah Miftahuljannah; Oky Hermansyah; Maria Eka Patri Yulianti; Tri Danang Kurniawan; Rose Intan Perma Sari (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
This study aims to analyze the relationship between the level of knowledge and attitudes of the community towards antibiotic use in Pondok Besi Village, Bengkulu City. This study used a quantitative method with an observational analytical design through a cross-sectional approach. The study sample consisted of 104 respondents obtained using proportional cluster random sampling technique. Data were collected through questionnaires that had been tested for validity and reliability, then analyzed using Univariate and Univariate analysis with the Chi-Square test. The results showed that the majority of respondents had a good level of knowledge (48.1%) and a good attitude (51.0%) towards antibiotic use. The Univariate analysis showed a significant relationship between knowledge and attitudes of the community, where respondents with better knowledge tended to have more positive attitudes towards antibiotic use. These findings indicate that knowledge plays an important role in shaping public attitudes towards the rational use of antibiotics. Therefore, continuous improvement of health education is essential to strengthen understanding and shape appropriate attitudes towards antibiotic use to prevent antimicrobial resistance at the community level.